WOMEN'S STUDY ON RANDAI SI RABUANG AMEH, AS AN EXISTENCE OF RANDAI DEVELOPMENT IN MINANGKABAU - Monita Precillia; Dedi Darmadi (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2022)
This article entitled "Development of the traditional art of randai into the creation of randai Si Rabuang Ameh by Zulkifli is a qualitative research in the form of descriptive analysis". The Si Rabuang Ameh performance is the result of the artist's observations and concerns about the women's desire to be directly involved in the randai performance. This paper aims to describe the background of the presence of the Si Rabuang Ameh performance, analysis of the work; innovation on randai and women's studies on randai si rabuang ameh, as a form of developing randai in Minangkabau. Minangkabau which adheres to a matrilineal system, of course, the participation of women in traditional randai performances is considered taboo. The Randai Si Rabuang Ameh show has been adapted so that it deserves to be a female randai. Randai Si Rabuang Ameh is a place for women who want to participate in randai performances. The randai creations in the Si Rabuang Ameh show do not eliminate the norms or customs and their traditional habitats so as not to damage the existence of randai as a traditional Minangkabau art. The performance of Randai Si Rabuang Ameh also does not conflict with the ethics of Contributing Duo Baleh in Minangkabau, so it does not become a debate or conflict with the participation of women in the show. The show that was innovated into women's randai, the wave motion was inspired by the motion of suduang daun, tanduak buang, jinjiang bantai, lapiah jarami, galatiak, gelek and others. Keywords: Si Rabuang Ameh; Randai; Women   KAJIAN PEREMPUAN TERHADAP RANDAI  SI RABUANG AMEH, SEBAGAI WUJUD PENGEMBANGAN RANDAI DI MINANGKABAU AbstrakTulisan berjudul pengembangan seni tradisi randai menjadi kreasi randai Si Rabuang Ameh karya Zulkifli ini merupakan penelitian yang bersifat kualitatif berbentuk diskriptif analisis. Pertunjukan Si Rabuang Ameh merupakan hasil observasi dan keresahan pengkarya terhadap keinginan kaum perempuan untuk terlibat langsung dalam pertunjukan randai. Tulisan ini bertujuan mendiskripsi latar belakang hadirnya pertunjukan Si Rabuang Ameh, analisis karya; inovasi terhadap randai dan kajian perempuan terhadap randai si rabuang ameh, sebagai wujud pengembangan randai di Minangkabau. Minangkabau yang menganut sistem matrilineal, tentunya keikutsertaan perempuan dalam pertunjukan randai tradisi di anggap tabu. pertunjukan randai Si Rabuang Ameh telah diadaptasi sehingga pantas menjadi randai perempuan. Randai Si Rabuang Ameh menjadi wadah bagi kaum perempuan yang ingin berpartisipasi dalam pertunjukan randai. Kreasi randai dalam pertunjukan Si Rabuang Ameh tidak mengilangkan norma atau pakam dan habitat ketradisiannya sehingga tidak merusak keberadaan randai sebagai kesenian tradisioal Minangkabau. Pertunjukan randai Si Rabuang Ameh juga tidak bertentangan dengan etika Sumbang Duo Baleh di Minangkabau, sehingga tidak menjadi perdebatan ataupun pertentangan terhadap keikutsertaan perempuan dalam pertunjukan. Pertunjukan yang di inovasi menjadi randai perempuan, gerak gelombang terinspirasi dari gerak suduang daun, tanduak buang, jinjiang bantai, lapiah jarami, galatiak, gelek dan lainnya.Kata kunci : Si Rabuang Ameh; Randai; Perempuan